The Effect of Regulations in an Endogenous Growth Model with Research and Development - VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields; Vol 13 No 1 (2022): TPREF, Volume XIII, Issue 1(25), Summer 2022DO - 10.14505/tpref.v13.1(25).04, 2022)
We utilize a relatively standard endogenous growth model with intermediaries and research and development (R&D). We augment the setup with government regulations to study the effect of regulations on aggregate allocations. The novelty is that we endogenize the problem of the regulator, so the number of regulations is determined within the model. Next, we solve the model and derive some comparative static results. The qualitative results confirm that more regulation leads to a lower number of intermediaries, but each of those is now larger. Investment in physical capital is higher, but that comes at the expense of lower investment in R&D, lower consumption, lower output, and lower welfare. Overall, the intuition that regulation is bad for the economy is confirmed.